(untitled) (Research, Society and Development, 2021)
Fluids in terms of rheological behavior can be classified into Newtonians and non-Newtonians. Newtonians are fluids that have unique and absolute viscosities, because the ratio between shear stress and shear rate is constant. In the oil industry, most fluids, such as microemulsions, oil and polymeric solutions, do not exhibit Newtonian behavior. To understand the behavior of chemical fluids, it is necessary to analyze some parameters to interpret their properties and applicability. In this context, the present work aims to obtain and characterize microemulsion systems containing Alkali, Surfactant, and Polymer, and verify their applicability in advanced oil recovery. Thus, we obtained five microemulsion systems consisting of saponified coconut oil (surfactant), Butan-1-ol (co-surfactant), kerosene (oil phase), Na2CO3 (alkali), water and different percentages of the polymer. The systems were characterized by analyzes of particle diameter, surface tension, viscosity and rheological behavior using mathematical models. Droplet sizes showed characteristic values of micellar aggregates. Surface tension presented a slight elevation when the percentage of polymer in the microemulsion increased. Through the rheological study, it was possible to observe that experimental values were better adjusted to the Ostwald-de Waele “power-law” model. As the percentage of polymer in the system increased, we calculated the apparent viscosity of the systems and observed an increasing change in viscosity values, a result of great interest to enhanced oil recovery studies.